2006
DOI: 10.1258/004947506778604904
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and echocardiographic study of hypertrophic cardiomyopathy in Tanzania

Abstract: There are few published reports of hypertrophic cardiomyopathy (HCM) in Africans, partly due to lack of Echocardiography machines at most hospitals. Among 6680 patients referred for echocardiography at Muhimbili National Hospital between June 1998 and October 2002, 134 (0.19%) patients had HCM. Their mean age was 54.8+/-14.2 years. In total 67.9% were men and 32.1% were women. Due to the diverse clinical features only eight (5.9%) patients had a correct diagnosis of HCM prior to their ECHO. The important role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 4 publications
2
9
0
Order By: Relevance
“…(1)(2)(3)(4) Surprisingly these studies yielded similar results with estimated hypertrophic cardiomyopathy prevalence of 0.2%…”
Section: Introductionsupporting
confidence: 75%
“…(1)(2)(3)(4) Surprisingly these studies yielded similar results with estimated hypertrophic cardiomyopathy prevalence of 0.2%…”
Section: Introductionsupporting
confidence: 75%
“…Hypertrophic cardiomyopathy (HCM), which was found in 0.2% of 6680 unselected echocardiograms in Tanzania,77 is recognised in Africans and other populations as an autosomal dominant disorder that is caused by mutations in at least 11 different genes that code for sarcomeric proteins 3. Most HCM-causing mutations have arisen independently in most families studied, suggesting that the majority occurred relatively recently as new mutations 30.…”
Section: Non-endemic Cardiomyopathiesmentioning
confidence: 99%
“…This impression was reinforced by a study that found HCM to occur in 0.2% of 6 680 unselected echocardiograms performed in Tanzania 3. However, recent echocardiographic studies from the continent have dispelled that myth 4.…”
Section: Introductionmentioning
confidence: 99%